2012
DOI: 10.7759/cureus.71
|View full text |Cite
|
Sign up to set email alerts
|

Celiac disease initially mis-diagnosed as irritable bowel syndrome: Case report

Abstract: Background: The increasing availability of serological testing & upper endoscopy has led to more frequent diagnosis of celiac disease & recognition that it may mimic Irritable bowel syndrome (IBS). Objective: The objective of the present case report is to describe the importance of screening those with vague abdominal symptoms (like patients with IBS) and iron deficiency anemia for celiac disease. Methods: We report the clinical course of a 30-year-old patient with vague abdominal symptoms initially misdiagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…CBT placement has the following advantages: (1) The insertion point is closer to the spinous process than traditional pedicle screws, so the incision required for exposure is smaller, and the damage to soft tissues and muscle dissection and traction operations is also less, which can reduce Bleeding during and after surgery improves the satisfaction of postoperative rehabilitation [12] ; (2) The direction of nail placement is insidedown-out-up, so the adjacent intervertebral joints are less infringed, and iatrogenic vertebral facet joint intrusion is reduced. Reduce the incidence of adjacent segmental disease [13] ; (3) The direction of screw placement is that the distal end of the screw is inclined to the cephalic and lateral sides, and the upward screw passage in the sagittal plane is away from the spinal cord, nerve roots, and dural sac to avoid injury Risk; at the same time, it is closer to the midline of the nail entry point, which avoids damage to the medial nerve branch [14,15] ; (4) The cortical bone part of the pedicle complex can be used to the greatest extent to provide a higher holding force , Anti-axial pullout and anti-torsion ability, thereby reducing the risk of screw loosening and screw withdrawal after surgery, and can be applied to patients with osteopenia and osteoporosis; At the same time, CBT screws still have some shortcomings in clinical application: (1) CBT screws x the middle and posterior columns of the spine, and cannot achieve the strength of three-column xation. Therefore, it is di cult for patients with severe vertebral damage and kyphosis Fixation and correction of kyphotic deformity; (2) The fatigue resistance of CBT screws is lower than that of traditional pedicle screws, and the special entry point and trajectory of CBT screws destroy the integrity of the isthmus and pedicle of the vertebral body.…”
Section: Discussionmentioning
confidence: 99%
“…CBT placement has the following advantages: (1) The insertion point is closer to the spinous process than traditional pedicle screws, so the incision required for exposure is smaller, and the damage to soft tissues and muscle dissection and traction operations is also less, which can reduce Bleeding during and after surgery improves the satisfaction of postoperative rehabilitation [12] ; (2) The direction of nail placement is insidedown-out-up, so the adjacent intervertebral joints are less infringed, and iatrogenic vertebral facet joint intrusion is reduced. Reduce the incidence of adjacent segmental disease [13] ; (3) The direction of screw placement is that the distal end of the screw is inclined to the cephalic and lateral sides, and the upward screw passage in the sagittal plane is away from the spinal cord, nerve roots, and dural sac to avoid injury Risk; at the same time, it is closer to the midline of the nail entry point, which avoids damage to the medial nerve branch [14,15] ; (4) The cortical bone part of the pedicle complex can be used to the greatest extent to provide a higher holding force , Anti-axial pullout and anti-torsion ability, thereby reducing the risk of screw loosening and screw withdrawal after surgery, and can be applied to patients with osteopenia and osteoporosis; At the same time, CBT screws still have some shortcomings in clinical application: (1) CBT screws x the middle and posterior columns of the spine, and cannot achieve the strength of three-column xation. Therefore, it is di cult for patients with severe vertebral damage and kyphosis Fixation and correction of kyphotic deformity; (2) The fatigue resistance of CBT screws is lower than that of traditional pedicle screws, and the special entry point and trajectory of CBT screws destroy the integrity of the isthmus and pedicle of the vertebral body.…”
Section: Discussionmentioning
confidence: 99%
“…Although data on the prevalence of CD in the Saudi adult population with IBS is scant, one study has reported the prevalence to be 9.6% [6] while it has been reported to be 2% in western societies [9] . In addition, only a few case reports of misdiagnosed CD cases in patients with IBS have been reported in the Saudi population [10,11] . In this case report, the initial patient clinical manifestations were misdiagnosed as IBS, however, the continuation of complaints (tiredness, insomnia, weight loss and depression) with IBS therapy necessitated a visit to the GI clinic to recommend screening for CD.…”
Section: Discussionmentioning
confidence: 99%